Connecting Green Consumption Value to Green Word-of-Mouth: Insights into SMEs’ Eco-Friendly Product Purchasing Dynamics - Religia, Yoga; Ramawati, Yussi; Said, Jamaliah (Jurnal Manajemen Bisnis, 2025)
Research aims: To examine the impact of different consumption values (functional, epistemic, emotional, social, and conditional) on green purchase behavior and green word of mouth, particularly within the context of green products like Jadah Tempe.Design/Methodology/Approach: A quantitative approach with a cross-sectional descriptive design was used using a questionnaire distributed to 200 respondents in Yogyakarta both online and offline. From the distributed questionnaire, complete data was obtained from 188 respondents to be used in the analysis process.Research findings: The findings indicate that emotional and conditional values significantly influence green purchase behavior and green word-of-mouth. Specifically, emotional values have a positive relationship with green purchase behavior, while conditional values demonstrate the strongest effect on consumer choices. Green purchase behavior serves as a crucial mediator in these relationships, suggesting that consumers with emotional attachments and contextually relevant values are more likely to engage in and promote sustainable purchasing.Theoretical Contribution/Originality: This research provides unique insights into the consumer behavior of Jadah Tempe, emphasizing local sustainable food products' importance and offering a foundation for future studies in sustainable consumption practices.Practitioners/Policy Implications: Marketers should focus on emotional connections and context in their campaigns to promote sustainability, enhancing consumer engagement with products like Jadah Tempe. Understanding the influence of emotional and conditional values on young consumers can help SMEs create inclusive marketing strategies that resonate with diverse segments and promote sustainable products.Research Limitations/Implications: Although this study is limited to the Yogyakarta region, it opens up opportunities for further research in other areas to understand different contexts. The findings of this study still make a strong contribution to understanding consumer behavior and provide a solid foundation for future studies.